Role of Formyl Peptide Receptors (FPR) in Abnormal Inflammation Responses Involved in Neurodegenerative Diseases - Mollica, Adriano; Stefanucci, Azzurra; Costante, Roberto; Pinnen, Francesco (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2012)
Neurodegenerative disorders, such as multiple sclerosis, prion diseases, Alzheimer's disease and Parkinson's disease are often associated with inflammatory process, which involves various components of the immune system in the central nervous system, in particular astrocytes and microglial cells. Inflammation mediators such as cytokines, leukotrienes, superoxide radicals, eicosanoids, the complement cascade, and FPR agonists (formyl peptides) may play a significant role in pro-inflammatory responses, in which infiltration of activated mononuclear phagocytes at the sites of lesion is a common feature. To prevent long-term inflammation damage, the central nervous system could be treated with antinflammatory agents such as non-steroidal anti-inflammatory drugs (NSAIDs), but only few drugs were found to be effective and their therapeutic benefits is limited by side effects. Accumulating evidences suggest that targeting glia-neuron system might be a therapeutic approach in the treatment of neurodegenerative disease progression, in particular of Alzheimer's disease. Aminopyridazine derivative discovered in unbiased cell-based screens for new synthetic compounds, have proved to be able to suppress selective glial activation responses via mechanisms distinct from NSAIDs. In this review, we report the potential involvement of FPR receptors in inflammatory responses and the potential use of their antagonists to modulate the inflammatory responses of the microglia. Recent results demonstrate that targeting of inflammatory glia cytokine pathways, can suppress Aβ-induced neuroinflammation in vivo, resulting in the attenuation of neuronal damage.
Keywords: SAA